(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The principal weapon of the cold war, which developed between the USA and the USSR after World War II and has grown in intensity over time, is the media, which is discussed in this article. It primarily discusses the early Western media’s impact on the USSR, the Soviet press’s response to such anti-communist ideas and their effects, as well as the factors that led to and contributed to the communist thought spreading throughout the entire Union.